Muhammadiyah sebagai Gerakan Islam, Dakwah, dan Tajdid Analisis Peran dan Dinamika Pembaruan dalam Konteks Modern - Fitriani Fitriani; Muhammad Rusmin (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Muhammadiyah is a modern Islamic organization that plays a strategic role in socio-religious transformation in Indonesia. This study aims to analyze Muhammadiyah as an Islamic movement, a da’wah movement, and a tajdid (renewal) movement within the context of contemporary society. This research employs a qualitative approach using library research methods. The findings reveal that Muhammadiyah functions not only as a normative religious organization but also as a transformative force that integrates the purification of Islamic teachings with modern dynamics. As an Islamic movement, Muhammadiyah emphasizes adherence to the Qur’an and Sunnah through ijtihad. As a da’wah movement, it develops institutional-based and sustainable preaching models. Meanwhile, as a tajdid movement, Muhammadiyah demonstrates adaptive capacity in responding to global challenges without losing its ideological identity.